2017
DOI: 10.2147/ijn.s141839
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles reduce high glucose-induced oxidative-nitrosative stress regulated inflammation and apoptosis via tuberin-mTOR/NF-κB pathways in macrophages

Abstract: Hyperglycemia is a risk factor for cardiovascular mortality and morbidity, and directly responsible for exacerbating macrophage activation and atherosclerosis. We showed that gold nanoparticles (AuNPs) reduce the high glucose (HG)-induced atherosclerosis-related complications in macrophages via oxidative-nitrosative stress-regulated inflammation and apoptosis. The effects of AuNPs on oxidative-nitrosative stress markers such as cellular antioxidants were attenuated by HG exposure, leading to reduction in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 47 publications
(64 reference statements)
1
24
0
Order By: Relevance
“…Specifically, MAT2B can alleviate apoptosis in various tumor cells. [51][52][53] In addition, overexpression of MAT2B is associated with the inhibition of mTOR, 54 which is a classic upstream promoter of NF-jB signaling, 55,56 suggesting that MAT2B may alleviate cellular apoptosis and NF-jB signaling controlled inflammatory response. Consequently, our research fully identified that miR-21-3p could aggravate BBB damage after TBI by promoting cellular apoptosis and inflammation through targeting MAT2B.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MAT2B can alleviate apoptosis in various tumor cells. [51][52][53] In addition, overexpression of MAT2B is associated with the inhibition of mTOR, 54 which is a classic upstream promoter of NF-jB signaling, 55,56 suggesting that MAT2B may alleviate cellular apoptosis and NF-jB signaling controlled inflammatory response. Consequently, our research fully identified that miR-21-3p could aggravate BBB damage after TBI by promoting cellular apoptosis and inflammation through targeting MAT2B.…”
Section: Discussionmentioning
confidence: 99%
“…There are also new and emerging therapeutic opportunities with nanoparticles. For example, in hyperglycemia, gold nanoparticles reduce inflammation and apoptosis through tuberin-mTOR/ NFκB pathway inhibition in macrophages (149). In cancer cells, Zn-CuO nanoparticles can induce autophagy and apoptosis through the NFκB pathway (150).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, hyperglycemia can cause nonenzymatic reactions of glucose with longer‐lived molecules, resulting in stable early glycosylation products. Then, they undergo a series of rearrangements, dehydration, and cleavage reactions to produce stable glycation end products, including G‐LDL, G‐HDL, and other glycosylated proteins . Glycosylated lipoprotein also promotes lipoprotein oxidation .…”
Section: Discussionmentioning
confidence: 99%